2005
DOI: 10.1271/bbb.69.2101
|View full text |Cite
|
Sign up to set email alerts
|

A Single Free Cysteine Residue and Disulfide Bond Contribute to the Thermostability ofAspergillus saitoi1,2-α-Mannosidase

Abstract: Aspergillus saitoi 1,2--mannosidase contains three conserved cysteine residues (Cys334, Cys363, and Cys443). We showed that Cys334 and Cys363 are involved in a disulfide bond, and that Cys443 contains a free thiol group. The cysteines were not essential for the activity analyzed by site-directed mutagenesis and kinetics. The substitution at each cysteine residue greatly destabilized the enzyme. The T m values of WT, C443A, C443G, C443S, and C443T were 55.8, 51.9, 50.2, 50.0, and 52.8 C respectively. The specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…The observed near-complete inhibition of endoglucanase activity by thiol inhibitors led us to investigate the role of free cysteines in the activity of Cel5R. Moreover, it has been shown that the substitution of free thiols with other amino acid residues increased30 the thermal stability of the protein in some cases, while in others it is decreased31. Thus, to understand the role of cysteines in Cel5R, different constructs with single, double and quadruple mutations (cysteine to alanine) were made and their activities were checked by DNS (3,5-Dinitrosalicylic acid) assay.…”
Section: Resultsmentioning
confidence: 99%
“…The observed near-complete inhibition of endoglucanase activity by thiol inhibitors led us to investigate the role of free cysteines in the activity of Cel5R. Moreover, it has been shown that the substitution of free thiols with other amino acid residues increased30 the thermal stability of the protein in some cases, while in others it is decreased31. Thus, to understand the role of cysteines in Cel5R, different constructs with single, double and quadruple mutations (cysteine to alanine) were made and their activities were checked by DNS (3,5-Dinitrosalicylic acid) assay.…”
Section: Resultsmentioning
confidence: 99%
“…saitoi , T. reesei , and P . citrinum class I 1,2‐α‐mannosidases have also been studied extensively 18,19,24,26–28 . The filamentous fungal enzymes belong to a functionally distinct subgroup of the class I enzymes that include the mammalian Golgi 1,2‐α‐mannosidases 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The deduced C. posadasii sequence 1,2‐α‐mannosidase protein sequence shares about 60% identity with other fungal class I 1,2‐α‐mannosidases and contains a number of conserved regions including a conserved glutamic acid residue at position 127 and two conserved cysteine residues (Cys‐337 and Cys‐366) 18,19 . The N‐terminal region of the deduced amino acid sequence contains a hydrophobic amino acid sequence, a putative transmembrane α‐helix, and a predicted cleavable signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disulfide bridge between C230 and C247 is important, C247 seems to be more significant than C230 for the stability of CARDS toxin ( Figure 3a). Previous studies have demonstrated that both disulfides and thiol groups have important roles in the stability of proteins (Burova, Choiset, Tran, & Haertle, 1998;Tatara, Yoshida, & Ichishima, 2005). It is possible that irrespective of its role in disulfide bond formation, the thiol form of C247 may also be essential to maintain the stability of the toxin.…”
Section: Discussionmentioning
confidence: 99%